Sensitivity Analysis of Factors Influencing Accelerometer Hysteresis Based on Morris Screening Method. Issue 1 (August 2021) - Ye, Kun; Teng, Lin; Li, Pengfei; Chen, Liang
Abstract: Aiming at the fuzzy cognition of the key process parameters that affect the accelerometer hysteresis performance in the assembly and manufacturing process, a sensitivity analysis method for the influencing factors of accelerometer hysteresis based on Morris screening method was proposed in this paper. Firstly, the assembly and manufacturing process parameters and their range of values of core structure pendulum components are analyzed statistically. Secondly, the mean value and variance of the basic factors of each parameter are obtained based on finite element numerical simulation method. The results show that the bonding Angle between the pad I and the pendulum plate and the bonding Angle between the counterweight and the pendulum plate have the greatest influence on the hysteresis performance of the accelerometer. The interaction between the counterweight and the bonding Angle and other parameters is the most nonlinear.